The effect of whey type on the yield and quality characteristics of Urda - Chadikovski, Aleksandar; null, null (Croatian Dairy Union, 2022)
In this research, whey cheese Urda was produced in industrial conditions by thermal denaturation, followed by protein aggregation and precipitation of whey which was obtained during production of white brined cheese and Kashkaval. The impact of milk pasteurization temperature, pH values, protein content, and whey type on the Urda quality and yield was examined. The impact of whey pH on Urda yield was evaluated in the pH range from 4.5 to 6.0. Urda yield reached a maximum pH value between 5.2 and 5.4. The highest Urda yield from white brined cheese whey was obtained at pasteurization temperature of 72 °C. By increasing the temperature to 80 °C, the whey protein content and the Urda yield decreased. Whey type had no significant impact on the sensory and textural characteristics of Urda. Urda was classified as a low-fat soft albumin cheese. Valorisation of whey generated after production of white brined cheese, and manufacturing of Urda with maximum yield and optimal functional properties, is not only of economic importance, but can be conducive to improve waste water quality.